2014
DOI: 10.1109/tvt.2013.2289889
|View full text |Cite
|
Sign up to set email alerts
|

A Vacation-Based Performance Analysis of an Energy-Efficient Motorway Vehicular Communication System

Abstract: Due to the unprecedented growth in bandwidth requirement, the increasing number of access points (APs) deployed within a macrocell for services such as video conferencing, video gaming, and data off-loading leads to significantly higher energy consumption. This advancement in mobile networks has forced researchers to explore various methods of energy saving, although with little emphasis on motorway vehicular networks where mobility is also an important aspect. Energy saving in these networks is extremely chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…A number of studies showed that by considering a sleep strategy at a node during its inactivity, a certain amount of energy can be saved [2], [5], [9], [12], [13], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies showed that by considering a sleep strategy at a node during its inactivity, a certain amount of energy can be saved [2], [5], [9], [12], [13], [14], [15].…”
Section: Related Workmentioning
confidence: 99%
“…Hence, a macro-micro cellular structure is considered in this paper, where a number of micro-cells are served by the Access Points (APs) / Roadside Units (RSUs) within a macro-cell served by a BS [4], making it feasible to operate various sleep strategies for energy savings at the APs/RSUs. One such strategy is sleep cycles where an RSU switches OFF only its transmitter part for a randomly distributed time duration when there is no request to serve [9]. The RSU remains in such mode for the entire time duration (randomly generated with a certain mean value) even if packets are waiting to be served, thus degrading the system performance.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations